The experience of passenger transport start-ups in greater Cairo: An analysis - Fakhr El-Din, Passant Ehab (AUC Knowledge Fountain, 2016)
This research explores start-ups that provide passenger transport services in Cairo, Egypt. It studies the various factors that affect these start-ups operations and lead to their survival or closure. It adopts a qualitative approach depending on both primary and secondary data, in-depth interviews conducted with different stakeholders with different roles, and content analysis. The findings cover a list of external and internal best practices that increases the probability of a transportation start-up's survival. The researcher recommends as well some means of Public Private Partnership that can be implemented in the transportation domain in Cairo, Egypt that might support these start-up's operations. The research enables the start-ups and the public sector to better understand the possible impacts of liaising with each other to reach a win-win situation for the sake of both the start-ups and the public sector, where the start-ups would operate the business smoothly and at the same time reduce the burden on the public sector as a public transport provider, thus lead to more effective operations.